Study of perinatal autopsies in tertiary care hospital 20 year experience - Kamakeri, N. S.; C. A., Ramalingappa; D., Vinayraju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Losing a baby is painful. Looking for answers can help. Although nothing can change the loss, a perinatal autopsy may offer answers to better understand what happened. A perinatal autopsy is a medical exam done on the fetus or infant to help explain the cause of death. This exam may also find the underlying reason for an illness, disease or birth defect. Methods: Babies of mothers with bad obstetrics history, died in utero, neonatal period and baby deaths of unknown cause were subjected for clinical autopsy in the last 20 years. Based on the major and associated pathological findings, an attempt was made to find the cause of death. Results: Immaturity of the organs found to be the most common cause for perinatal death. Meconium aspiration pneumonia, external congenital abnormalities are found to be the other common causes for perinatal mortality. Conclusions: Perinatal autopsies are the effective method of finding the cause of perinatal death, and helps to some extent in preventing the future loses.